Equal Opportunity to Meaningful Competitions: Disability Rights and Justice in Sports - Mika LaVaque-Manty (Disability Studies Quarterly, 2005)
This paper explores the questions of equality and social justice for people with disabilities in sports and, by extension, other civil societal practices that involve the pursuit of excellence. I argue that such practices come within the purview of justice depending on the interplay between political activism, institutionalized anti-discrimination statutes such as the ADA, and the internal norms of a practice. There are many ways to interpret the ADA, and a successful argument for a right to a pursuit of excellence requires that the ADA be understood as an anticaste principle. That interpretation allows me to show how even voluntary, ostensibly apolitical social practices can stigmatize groups of people — people with disabilities, for example — and how such practices can be refigured to bring about social justice.
Keywords: disability sport; Paralympics; ADA; equal opportunity